1999
DOI: 10.1046/j.1365-2249.1999.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenotype and cytokine profiles of T cell lines derived from vitreous humour in ocular inflammation in man

Abstract: Intermediate uveitis (IU) and Fuchs' heterochromic cyclitis (FHC) are two chronic ocular inflammatory disorders. They differ considerably in ocular morbidity, which is higher in IU. T cell lines were derived from the vitreous humour (VH) and peripheral blood (PB) of 10 patients with IU and four patients with FHC. There was a predominance of CD8+ in all the lines. However, there was a significantly higher percentage of CD4+ T cells in the T cell lines derived from VH of IU (32.0 +/- 8.6%) compared with FHC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 40 publications
0
50
0
2
Order By: Relevance
“…A significantly higher percentage of CD4 + T cells were also present in the T-cell lines derived from patients with idiopathic uveitis as compared to those with FHC. 91 A positive correlation between IL-4 and IL-5 has also been demonstrated with IL-6 levels unchanged as compared to controls but significantly decreased as compared to patients with idiopathic uveitis. 13,14 In the aqueous humor of FHC uveitis patients, TGF-β2 has been detected at significantly lower levels than control groups.…”
Section: Ankylosing Spondylitismentioning
confidence: 84%
See 3 more Smart Citations
“…A significantly higher percentage of CD4 + T cells were also present in the T-cell lines derived from patients with idiopathic uveitis as compared to those with FHC. 91 A positive correlation between IL-4 and IL-5 has also been demonstrated with IL-6 levels unchanged as compared to controls but significantly decreased as compared to patients with idiopathic uveitis. 13,14 In the aqueous humor of FHC uveitis patients, TGF-β2 has been detected at significantly lower levels than control groups.…”
Section: Ankylosing Spondylitismentioning
confidence: 84%
“…79,95 In humans, IL-4 has only been detected in low levels and at levels not significantly different from controls in the aqueous humor and serum of patients with idiopathic uveitis. 86 91 A recent study also showed that there were no significant differences in aqueous humor IL-4 levels between anterior uveitis, panuveitis and control groups, but that IL-5 was significantly not detected in the panuveitis groups with idiopathic uveitis as compared to controls and those with idiopathic anterior uveitis. 14 A decrease in aqueous humor IL-10 has been demonstrated in conjunction with an increase in activated CD4 + T cells in anterior uveitis, which could partially explain why in acute anterior uveitis, the inflammation is more severe.…”
Section: Cytokines and Chemokines In Patients With Uveitismentioning
confidence: 96%
See 2 more Smart Citations
“…4,5,[9][10][11][12][17][18][19] A possible explanation for these results could be the restoration of an immunological homeostasis by the mechanical removal of the vitreous body with captured autoreactive T cells and proinflammatory cytokines during PPV. 24,25 The replacement of the vitreous with aqueous humor and its numerous immunomodulatory factors after PPV may have an additional regulatory effect. 26 In contrast, the need for systemic steroids and immunomodulatory treatment showed no significant difference before and after PPV.…”
Section: Discussionmentioning
confidence: 99%